2004
DOI: 10.1103/physreve.69.031803
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and phase diagram of complex block copolymers:  ABC linear triblock copolymers

Abstract: Using a real space implementation of the self-consistent field theory for the polymeric system, we explore microphases of ABC linear triblock copolymers. For the sake of numerical tractability, the calculation is carried out in a two-dimensional (2D) space. Seven microphases are found to be stable for the ABC triblock copolymer in 2D, which include lamellae, hexagonal lattice, core-shell hexagonal lattice, tetragonal lattice, lamellae with beads inside, lamellae with beads at the interface, and hexagonal phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
203
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(219 citation statements)
references
References 31 publications
15
203
1
Order By: Relevance
“…We found that these linear and star-shaped ABC terpolymers self-assemble into lamellar phases when using these parameters (Figure 3). The calculations agree with those of Yang et al [18,19] In our simulation, we select the relative deformation from À0.15 to + 0.15, and the corresponding free energies (the free energy of extension or shear) are calculated. Table 1 lists the dimensionless tensile moduli, obtained from Equation (17) for the triblock copolymer system, of lamellar structures having different molecular architectures (linear and star).…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…We found that these linear and star-shaped ABC terpolymers self-assemble into lamellar phases when using these parameters (Figure 3). The calculations agree with those of Yang et al [18,19] In our simulation, we select the relative deformation from À0.15 to + 0.15, and the corresponding free energies (the free energy of extension or shear) are calculated. Table 1 lists the dimensionless tensile moduli, obtained from Equation (17) for the triblock copolymer system, of lamellar structures having different molecular architectures (linear and star).…”
Section: Resultsmentioning
confidence: 70%
“…Consequently, the internal energy U should be written as being inversely proportional to the equilibrium domain size d*, that is, the thickness of the lamellae [Eq. (18)]: [32] U…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the volume fraction of the middle block C is between 0.4 and 0.5 and that of the end block is about 0.2, the separated stable phase is two interpenetrating tetragonal lattices (CST 2 ). The similar phase (TET 2 ) was predicted theoretically [11,33] and observed experimentally [17][18][19] in the linear ABC triblock copolymer. The difference is that the adjacent blocks, A and B, form the core-shell phase, then form the core-shell tetragonal lattice, and the other minority D forms the other tetragonal lattice which interpenetrates the core-shell tetragonal lattice.…”
Section: Symmetrical Interaction Parametersmentioning
confidence: 69%
“…Until now, the morphologies and the phase diagrams for AB diblock copolymers, linear ABC triblock copolymer, and even ABC threemiktoarm copolymers have been intensively studied theoretically and experimentally. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Moreover, the more complicated block copolymers, such as those of linear ABCA, [20] ABCD, [21][22][23][24][25] ABCDE [23] types, and ABCD four-miktoarm star copolymer, [26] have been synthesized. Among these complicated tetrablock copolymers, only the morphology of the linear ABCA tetrablock copolymers has been studied theoretically; [27,28] a substitution of the end block A by a different block D, such as is the case Summary: We studied the two-dimensional (2D) microphase-separated morphology of linear ABCD tetrablock copolymers by self-consistent field theory.…”
Section: Introductionmentioning
confidence: 99%